A cultural analysis of the visual signs in the Zapatistas websites - Escalona Urenda, Sandra (2012)
A political movement initiated in Mexico known as Zapatism is analysed through the visual objects displayed in their websites on the Internet. The objective is to make a cultural analysis and interpretation of the visual representation of Zapatistas websites, to expose their visual identity through the most salient visual signs and their corresponding cultural meanings. The analytical method introduced in this study is divided in three major aims: consolidating a pool of images retrieved from Zapatistas websites, finding patterns of visual elements within these images, and providing an interpretation for the visual signs emerging from such patterns. In the analysis, three images emerged as the core of the visual identity: the pasamontañas (black ski-mask), Subcomandante Marcos, and the red star. The main contribution of this work is the methodology and how it can be applied to support a discussion about the implications of the global-local cultural context for the visual elements of Zapatism online.